Domain‐General Learning and Memory Substrates of Reading Acquisition. Issue 2 (10th January 2020) - Earle, F. Sayako; Del Tufo, Stephanie N.; Evans, Tanya M.; Lum, Jarrad A. G.; Cutting, Laurie E.; Ullman, Michael T.
ABSTRACT: Prior research has demonstrated that linguistic skills and knowledge contribute to successful reading acquisition. In contrast, little is known about the influence of domain‐general learning abilities on reading. To investigate associations between general memory functions and reading during the early stages of learning to read, performance measures of word‐level reading and of declarative and procedural learning were obtained in a cohort of 140 children, annually during their first 4 years of school. We hypothesized that differences in learning task performance would relate to reading ability in the early years, when children are first learning to read. We employed a series of linear mixed effects models to test the relationships between learning abilities and reading across time. Declarative learning performance predicted reading ability in first grade, while procedural learning performance predicted reading ability in second grade. Our findings suggest that reading acquisition may depend in part on general capacities for learning.